Sequence and Expression of Two cry8 Genes from Bacillus thuringiensis INTA Fr7-4, a Native Strain from Argentina - Navas, Laura Emilce (2014)
We found and characterized two cry8 genes from the Bacillus thuringiensis strain INTA Fr7-4 isolated in Argentina. These genes, cry8Kb3 and cry8Pa3 , are located in a tandem array within a 13,200-bp DNA segment sequenced from a preparation of total DNA. They encode 1,169- And 1,176-amino-acid proteins, respectively. Both genes were cloned with their promoter sequences and the proteins were expressed separately in an acrystalliferous strain of B. thuringiensis leading to the formation of ovoid crystals in the recombinant strains . The toxicity against larvae of Anthonomus grandis Bh. (Coleoptera: Curculionidae) of a spore-crystal suspension from the recombinant strain containing cry8Pa3 was similar to that of the parent strain INTA Fr7-4.